Predictive and Contemporaneous Power of the Determinants of Stock Liquidity - Xie, Linyin; Jin, Yuanqing; Mo, Chanxuan (Frontiers in Psychology, 2022)
This research constructs nine idiosyncratic variables and five systematic variables. A-shares from January 2003 to September 2021 are selected to study stock liquidity in the Chinese market. This research newly finds that only idiosyncratic part of stock return variance decreases stock liquidity. Idiosyncratic stock return decreases contemporaneous stock liquidity, but it has reversal for stock liquidity prediction. Market return plays more important role on contemporaneous and future stock liquidity than macro-economy, which influences through the channel of individual return and variance. Idiosyncratic factors are more important than systematic factors for contemporaneous and future stock liquidity. The predictive power of determinants decreases with the forecast length. The sensitivities of stock liquidity to some contemporaneous variables increase with the heightened EPU. The predictive and contemporaneous power of determinants for stock liquidity is robust over sub periods and with different liquidity measures.